The Preventive Role of Hydrogen-Rich Water in Thioacetamide-Induced Cholangiofibrosis in Rat Assessed by Automated Histological Classification - Li, Chaofu; Zhao, Xing; Gu, Xiaoqiang; Chen, Ying; Yu, Guanzhen (Frontiers in Pharmacology, 2021)
Background Cholangiofibrosis is a controversial intrahepatic cholangial lesion that precedes the development of cholangiocarcinoma. Here, we demonstrate that molecular hydrogen (H2) can be used to effectively prevent cholangiofibrosis. Methods The safety and quality of life (QOL) of rats was firstly evaluated. H2 was administered to rats subjected to thioacetamide (TAA)-induced cholangiofibrosis throughout the whole process. Then, rats were administrated with TAA for 3 months and then followed by H2 intervention. Rat livers were harvested and assessed by light microscopy and convolutional neural network. RNA-seq was performed to analyze the genetic changes in these animal models. Results Continuous use of H2-rich water was safe and improved QOL.The incidence and average number of cholangiofibrosis in the liver were higher in the TAA group (100%, 12.0±10.07) than that in the H2 group (57.1%, 2.86±5.43). The AI algorithm revealed higher Alesion/Aliver in the TAA group (19.6%±9.01) than that in the H2 group (7.54%±11.0). RNA-seq analysis revealed that H2 results in a decline in glycolysis. Moreover, in the third experiment, the incidence of microscopic or suspicious tumors and the ratio of liver lesions was decreased after long-term use of H2 (12.5%, 0.57%±0.45) compared with untreated group (100%, 0.98%±0.73). A number of intestinal microbiota was changed after H2 usage, including clostridiaceae_1, ruminococcus, turicibacter, coriobacteriales, actinobacteria, and firmicutes_bacterium. Conclusion Hydrogen-rich water protects against liver injury and cholangiofibrosis and improved quality of life partially through regulating the composition of intestinal flora.